New Approach to Spirituality (practical use) Counterpoint to materialist maxim “All spirituality is unreal” – spirituality with real world context (Muzafer Sherif) and Practical Use (William James) J E Kennedy "Very little research" on people - Charles Peck Jr (2011)
Dr Farra “Our models are out reality. But our models are not reality!" That coincides with the immortal philosopher Kant who argue we do not perceive the real world – but “representations” of the real world. Similarly, Bargh - from unconscious research - emphasizes mental categories and norms/stereotypes. Jung emphasizes symbols – which he argues are outside cognitive appraisals. "Models" are vital. spirituality counterpoint to the materialist maxim that "All spirituality is unreal" - new categories 1. Spirituality of Compassion: 2. Musical Spirituality - It is remarkable just how many studies of music as spirituality and as an evolutionary adaptive trait pivotal in the development of human society. Shulkin and Raglan observe "Our evolution is tightly bound to music 3. Prophecy, Poetry, "The prophet is a poet. His experience is one known to poets. What poets know as poetic inspiration; the prophets call divine revelation" - Heschel 4. Kapwa-loob pro-social norms/spirituality Kapwa & Relational Spirituality: shared identity, an inner self, shared with others…. unity of the self and the other Kapwa-loob are two unique aspects to culture in the Philippines 5. Children’s Spirituality Donna Thomas: “ Whether ‘positive’ or ‘negative’, anomalous experiences can catalyze self-healing for children and young people.greater self-awareness and a sense of intra-connectedness between self, others and the world.” 6. Artistic Spirituality: 7. Healing Spiritual-Psychic Experiences in Grieving - individuals do seem to cope better if they can "actualize" their spiritual experiences in times of crisis. 8. T’boli Dream Weaving/T’nalak – Dreams as a source of divine inspiration - "T’boli is a sacred spiritual tradition. Be Lang Dulay, with her over 100 different T’nalak designs." 9. Arctic Hunter Gatherer beliefs in animal spirits as "Human relationships with the natural world." 10. Dr. Ingela Visuri: Spirituality and "The Case of High functioning Autism"